Optimasi Formulasi Masker Gel Peel-off dengan Ekstrak Kulit Putih Buah Semangka (Citrullus lanatus) menggunakan Variasi Konsentrasi Karbopol 940: Optimization of the Peel-off Gel Mask Formulation with Watermelon (Citrullus lanatus) White Peel Extract Using Variations in Carbopol 940 Concentrations - Widyani Budiarti; Hermini Tetrasari; Neni Rahmani; Dita Andhyni (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2025)
Antioxidant compounds were known to reduce the reactivity of free radicals, thereby helping to prevent damage to cells and bodily molecules. These compounds were commonly found in various plants and fruits and were considered relatively safer than synthetic antioxidants. In this study, the author utilized white rind extract of watermelon (Citrullus lanatus) as a natural antioxidant source in the formulation of a peel-off  gel face mask intended for dry skin, using different concentrations of carbopol  940 as a gelling agent. An experimental method was employed, involving formulation development and product evaluation. Based on the assessment of three peel-off  mask formulations containing 3.5% watermelon white rind extract, the optimal concentration of carbopol  940 was determined to be 0.5%. This conclusion was drawn from evaluations of homogeneity, organoleptic properties, spreadability, pH, viscosity, drying time, and product stability. The peel-off  gel face mask formulated with 0.5% carbopol  940 and watermelon rind extract appears safe based on pH range and physical tests; however, further safety assessments. Keywords: Carbopol  940; Extract; Watermelon white rind; Face mask.